The Effect of Once-Daily Gabapentin Extended Release Formulation in Patients With Postamputation Pain - Knezevic, Nebojsa Nick; Aijaz, Tabish; Candido, Kenneth D.; Kovaleva, Svetlana; Lissounov, Alexei; Knezevic, Ivana (Frontiers in Pharmacology, 2019)
Objectives: To compare gabapentin extended-release, a gastro-retentive formulation, in relieving postamputation pain among gabapentin-experienced and gabapentin-naive patients. Design: Open-labeled pilot study Subjects: Sixteen patients with postamputation pain (8 patients in the gabapentin-experienced and 8 patients in the gabapentin-naive groups) Methods: Patients were started on gabapentin extended-release and followed up for 8 weeks. Patients reported their pain severity during rest and movement using a numeric rating scale (NRS), interference of pain with daily activities using the modified brief pain inventory (MBPI) questionnaire, and treatment satisfaction using the treatment satisfaction questionnaire for medication (TSQM). Results: Patients from both the gabapentin-experienced and gabapentin-naive groups achieved a significant and sustainable pain relief over the course of therapy. The pain scores at rest decreased in both gabapentin-experienced and gabapentin-naive groups from 5.88±1.36 and 4.88±2.95 to 1.88±0.99 and 1.38±1.51, respectively. An average percent of pain relief with gabapentin extended-release was noted to be significant (p<0.01) after 8 weeks of therapy among gabapentin-experienced (81.25±16.42%) and gabapentin-naive groups (85±17.73%) when compared to baseline for gabapentin-experienced (31.25±29%) and gabapentin-naive groups (36.25±34.2%) respectively. Gabapentin-experienced and gabapentin-naïve groups had no significant difference in global satisfaction from treatment (79.14±10.47 and 83.3±20.82), convenience of treatment (73.78±19.04 and 90.44±11.66), effectiveness of treatment (72.6±10.1 and 79.73±11.6). The only statistically significant difference among gabapentin-experienced and gabapentin-naive groups was found in adverse event tolerability (65.78±10.36 and 85.8±10.14, p<0.01). Conclusion: Once-daily dosing of gabapentin-extended release showed significant improvement in pain severity and functional status, with no difference found between gabapentin-experienced versus gabapentin-naive patients.